The Combined Effect of Rib with Single Large Eddy Break Up Devices on Flow and Heat Transfer Characteristic of Turbulent Flow in Rectangular Duct - Fayyedh, Ekhlas Mohammed; Hasan, Moayed R.; Mohammed, Ali Falah (Al-Nahrain Journal for Engineering Sciences, 2017)
An experimental investigation has been performed to study the effect of combined artificially roughened (ribs) with and without single Large Eddy Break-Up Devices, on flow and heat transfer characteristic of fully developed turbulent flow in rectangular duct. The aspect ratio of rectangular duct is 10, hydraulic diameter 72.72 mm, relative roughness pitch (P/e) 10 and relative roughness height (e/Dh) 0.05. The rib was in the form of circular shape with diameter of (4mm) which was mounted on heated wall of duct at spanwise direction. The experiments have been conducted by varying airflow rate in terms of Reynolds number ranging from 3.2x104 to 6.2x104 and constant heat flux of 600W/m2. The heat transfer and friction factor of the flow for rib and combined method were compared with those of a smooth duct under similar experimental conditions. It has been found that the combined method (rib with single Large Eddy Break-Up Devices) has significant effect on the friction factor and heat transfer with decreasing in friction factor with percent(1.2) and increasing Nusselt number with (4.1). Correlations for Nusselt number and friction factor in terms of (Reynolds number and Large Eddy Break-Up Devices) parameters are found which reasonably correlate the experimental data.